Staphylococcus aureus Augments Release of Matrix Metalloproteinase-8 from Human Polymorphonuclear Leukocytes - Klaus Kirketerp-Møller; Thomas Bjarnsholt; Peter Østrup Jensen; Magnus S. Ågren (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)